Epigastric hernia contiguous with the laparoscopic port site after endoscopic robotic total prostatectomy. Issue 4 (23rd March 2018) - Moriwaki, Yoshihiro; Otani, Jun; Okuda, Junzo; Maemoto, Ryo
Abstract: Both laparoscopic and endoscopic robotic surgery are widely accepted for many abdominal surgeries. However, the port site for the laparoscope cannot be easily sutured without defect, particularly in the cranial end; this can result in a port‐site incisional hernia and trigger the progressive thinning and stretching of the linea alba, leading to epigastric hernia. In the present case, we encountered an epigastric hernia contiguous with an incisional scar at the port site from a previous endoscopic robotic total prostatectomy. Abdominal ultrasound and CT revealed that the width of the linea alba was 30–48 mm. Previous CT images prepared before endoscopic robotic prostatectomy had shown a thinning of the linea alba. We should be aware of the possibility of epigastric hernia after laparoscopic and endoscopic robotic surgery. In laparoscopic and endoscopic robotic surgery for a high‐risk patient for epigastric hernia, we should consider additional sutures cranial to the port‐site incision to prevent of an epigastric hernia.